(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Goats in the tropics are often reared under the traditional extensive and semi-intensive management systems. These and other factors influence the pattern of pneumonia complex in goats. We investigated the bronchoalveolar lavage fluid (BALf) cellular changes and haematological response in different types of caprine pneumonia in Nigeria. Haematological indices and BALf cells were analysed from 300 goats randomly selected from 700 goats comprising different breed, age and body scores. The pneumonia status was well characterised using standard pathological tools. Data is summarized as Mean ± SEM and compared using non-parametric statistics at 5% significance. There was leukocytosis in the pneumonic animals. The overall lavage recovery rate was 55.5%. The differences in Haemoglobin concentration, and Lymphocyte-Neutrophil ratio were significant (p<0.05). BALf changes in the neutrophil, macrophage and eosinophil counts were significantly different (p<0.05). The diagnostic features including increased percentage neutrophils, Macrophage-Neutrophil ratio and eosinophils observed in BAL were reliable and also correlated positively to the pathological findings. BAL should be considered a component of the diagnostic approach to caprine pneumonia complex, as it may accurately aid diagnosis and identification of the causal organisms.